2013
DOI: 10.1111/plb.12109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen, phosphorus and potassium availability on emergence, nodulation and growth of Trifolium medium L. in alkaline soil

Abstract: Little is known about the effects of nutrient availability on the growth of Trifolium medium in alkaline soil. In 2010, a pot experiment (10 N, P and K fertiliser treatments) with seeding of T. medium into alkaline soil was performed and emergence of seedlings, survival, aboveground and belowground organs were studied. The positive effects of increased nutrient availability on seedling emergence ranged from 5% in the control to 17% in the high P treatment. The lowest mortality was in treatments with P and K su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…The present study showed that while seedlings with phosphorus and potassium supply maintained survival at a high rate, nitrogen fertilization decreased survival rate with an increasing prevalence of dead seedlings as the dose increased. Similar negative effects of a larger nitrogen supply on survival was also reported in Trifolium medium L. ( Chmelíková & Hejcman, 2014) and in Eucalyptus pauciflora Sieber ex Sprengel ( Atwell et al , 2009). Likewise, in Betula pubescens Ehrh., Larix sibirica Ledeb., and Picea sitchensis (Bong.)…”
Section: Discussionsupporting
confidence: 76%
“…The present study showed that while seedlings with phosphorus and potassium supply maintained survival at a high rate, nitrogen fertilization decreased survival rate with an increasing prevalence of dead seedlings as the dose increased. Similar negative effects of a larger nitrogen supply on survival was also reported in Trifolium medium L. ( Chmelíková & Hejcman, 2014) and in Eucalyptus pauciflora Sieber ex Sprengel ( Atwell et al , 2009). Likewise, in Betula pubescens Ehrh., Larix sibirica Ledeb., and Picea sitchensis (Bong.)…”
Section: Discussionsupporting
confidence: 76%